Sense and Sensibility: Of Dissonance for Organizational Innovations - Елена Владимировна Богданова (Journal of Economic Sociology, 2010)
Attracting the results of three ethnographic research projects, David Stark demonstrates the importance of heterarchy for organizational innovation. Heterarchies are resulted from recombination of actors’ spatial location, job status, technical systems, tools and evaluation principles of organizational goods while searching for the new and trying to organize dissonance generated by diversity of evaluation principles. Evaluation principles improve organization’s adaptability to any environmental and social changes.